Management of corneal wounds: some practical tips - Lee, SH (Nepalese Journal of Ophthalmology, 2010)
Corneal trauma is one of the leading causes of ocular morbidity. This paper aims at providing some practical tips useful for management of corneal wounds. DOI: 10.3126/nepjoph.v1i2.3693 Nep J Oph 2009;1(2):146-150